Built environment effects on fuel consumption of driving to work: Insights from on-board diagnostics data of personal vehicles - Zhu, Wanjing; Ding, Chuan; Cao, Xinyu (Transportation research. Part D, Transport and environment, 2019)
•This study examines the correlates of fuel consumption of naturalistic driving.•The built environment effect is through driving distance, speed and driver behavior.•The workplace built environment has a more important effect than residential one.•Job-housing balance may help reduce fuel consumption of commuting. Concerns over climate change and peak oil motivate examining the relationship between the built environment (BE) and individual fuel consumption. Most studies overlook BE characteristics at workplace locations. They often estimate fuel use based on travel distance instead of on actual consumption. This practice ignores other influential mechanisms. This study uses the naturalistic driving data of 660 personal vehicles in Beijing. We apply a structural equations model to examine multiple mechanisms under which the residential and workplace BE affects fuel consumption directly and indirectly through driving distance, travel speed, and driver behavior, controlling for the effect of the street environment along the commute route. We found that all three mediating variables are associated with vehicular fuel consumption for the commute. The workplace BE has the more important effect on fuel consumption than the residential BE, particularly regarding the distance from the workplace to the city center. This study highlights the role of job-housing balance in commuting fuel consumption reduction.